Immobilization of Antibodies by Genetic Fusion to a Fungal Self-Assembling Adhesive Protein - Stanzione, Ilaria; Izquierdo-Bote, Daniel; González García, María Begoña; Giardina, Paola; Piscitelli, Alessandra (Frontiers in Molecular Biosciences, 2021)
Although antibody immobilization onto solid surfaces is extensively used in several applications, including immunoassays, biosensors and affinity chromatography, some issues are still challenging. Self-assembling protein layers can be used to coat easily different surfaces by direct deposition. A specific bio-functional layer can be formed using genetic engineering techniques to express fused proteins acting as self-immobilizing antibodies. In this work, fusion proteins combining the self-assembling adhesive properties of a fungal hydrophobin, and the functionality of the single chain fragment variables (ScFvs) of two antibodies were produced. The chosen ScFvs are able to recognize marine toxins associated with algal blooms, saxitoxin and domoic acid, which can bioaccumulate in shellfish and herbivorous fishes causing food poisoning. ScFvs fused to hydrophobin Vmh2 from Pleurotus ostreatus were produced in Escherichia coli and recovered from the inclusion bodies. The two fusion proteins retained the functionality of both moieties, being able to adhere on magnetic beads and to recognize and bind the two neurotoxins, even if with different performances. Our immobilization procedure is innovative, and very easy to implement because it allows the direct functionalization of magnetic beads with ScFvs, without any surface modification. Two different detection principles, electrochemical and optical, were adopted, thus achieving a versatile platform suitable for different antigen detection. The sensitivity of the saxitoxin optical biosensor (LOD 1.7 pg/mL) is comparable to the most sensitive saxitoxin immunosensors developed until now.